THE DETERMINANT OF MCMORAN STOCK PRICE - Resky Rumbiak; Noer Azam Achsani; Trias Andati (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
The Purpose of this paper is to research the determinant of fundamental factors consisting of Net Profit Margin (NPM), Return on Equity (ROE), Return on Asset (ROE), Earning per Share (EPS), Working Capital Turn Over (WCTO) and external factors namely: oil prices, gold prices, the Fed’s interest rate and systematic risk, and also Indonesia government regulation towards FCX stock prices. This paper utilizes the ECM analysis methodology, the data during the period of 2000-2019, are obtained from quarterly financial statements issued to the Security Exchange Commission (SEC), the internet for share and commodity prices and also created dummy variable to accommodate the impact of Indonesia government regulation (MINERBA LAW). The results indicate that fundamental and external factors simultaneous have a significant influence on FCX stock prices. Partially in the long-term ROA, gold prices and world oil prices have a significant positive effect, while the Fed Rate and government policies have a significant negative effect. In the short term, the price of oil, gold and WCTO has a significant positive effect, while ROE has a significant negative effect. Keywords: external factors, fundamental factors, minerba law, mining company, stock price